2014
DOI: 10.13053/cys-18-2-2014-032
|View full text |Cite
|
Sign up to set email alerts
|

Feature Selection for Microarray Gene Expression Data Using Simulated Annealing Guided by the Multivariate Joint Entropy

Abstract: Abstract-In this work a new way to calculate the multivariate joint entropy is presented. This measure is the basis for a fast information-theoretic based evaluation of gene relevance in a Microarray Gene Expression data context. Its low complexity is based on the reuse of previous computations to calculate current feature relevance.The µ-TAFS algorithm -named as such to differentiate it from previous TAFS algorithms-implements a simulated annealing technique specially designed for feature subset selection. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…6 and 7, respectively. It was concluded that the performance of the proposed method, in terms of accuracy and efficiency, is better than other methods reported in literature (Dash, 2018;Gonzalez-Navarro and Belanche-Muñoz, 2014).…”
Section: Resultsmentioning
confidence: 61%
“…6 and 7, respectively. It was concluded that the performance of the proposed method, in terms of accuracy and efficiency, is better than other methods reported in literature (Dash, 2018;Gonzalez-Navarro and Belanche-Muñoz, 2014).…”
Section: Resultsmentioning
confidence: 61%
“…The main advantage of SA is that it allows up-hill moves in the iteration to avoid being stuck at a local minimum. SA has been widely used as a supervised or unsupervised feature subset selection method in data mining techniques, especially for microarray gene classification in biomedical data analysis [ 41 43 ]. Inspired by those works, in this study, we developed a novel hybrid feature selection method by hybridizing SA with an artificial neural network (ANN).…”
Section: Methodsmentioning
confidence: 99%